1997
DOI: 10.1016/s0005-2736(97)00061-8
|View full text |Cite
|
Sign up to set email alerts
|

A biotinylated perfringolysin O derivative: A new probe for detection of cell surface cholesterol

Abstract: theta-Toxin is a cholesterol-binding, pore-forming cytolysin of Clostridium perfringens. To detect cell surface cholesterol, we prepared a theta-toxin derivative, BC theta by biotinylation of a protease-nicked theta-toxin, which has the same binding affinity for cholesterol as theta-toxin without cytolytic activity. Human erythrocytes, V79 cells and human umbilical vein endothelial cells (HUVEC), were stained with BC theta coupled with FITC-avidin, and then the cells were analyzed by either flow cytometry or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 41 publications
1
68
0
Order By: Relevance
“…Filipin complex from Streptomyces filipinensis (F9765) was purchased from Sigma-Aldrich (St. Louis, MO). BC 20 was provided by Dr. Yoshiko Ohno-Iwashita (Cellular Signaling Group, Tokyo Metropolitan Institute of Gerontology, Tokyo, Japan). High performance silica gel 60 thin layer chromatographic plates were from Merck (Darmstadt, Germany).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…Filipin complex from Streptomyces filipinensis (F9765) was purchased from Sigma-Aldrich (St. Louis, MO). BC 20 was provided by Dr. Yoshiko Ohno-Iwashita (Cellular Signaling Group, Tokyo Metropolitan Institute of Gerontology, Tokyo, Japan). High performance silica gel 60 thin layer chromatographic plates were from Merck (Darmstadt, Germany).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…2 and 3) based on several lines of evidence including one that CDCs are not cytolytically active on cholesterol-deficient membranes and another that the depletion of membrane cholesterol reduces the extent of membrane binding to various eukaryotic cell types (4). Many studies, primarily performed with perfringolysin O (PFO), have shown that membrane binding is sensitive to the loss of cholesterol (4)(5)(6)(7)(8)(9)(10)(11) and that derivatives of PFO have been used as probes for membrane cholesterol (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…To understand the role of rafts in various cellular functions, identification and analysis of the molecular organization of cholesterol in rafts are essential. Cholesterol-binding toxin would be a useful tool for such a purpose (11).…”
mentioning
confidence: 99%